1997
DOI: 10.5694/j.1326-5377.1997.tb138695.x
|View full text |Cite
|
Sign up to set email alerts
|

Crying in hospitals: a survey of doctors', nurses' and medical students' experience and attitudes

Abstract: ObjectiveTo investigate doctors', nurses' and medical students' experiences with, and attitudes of health care personnel towards, crying in hospitals. DesignDescriptive, cross‐sectional study, using self‐report questionnaires. Setting and participantsThe sample comprised 52 doctors (response rate, 33%) and 103 nurses (response rate, 58%) from three Sydney metropolitan general hospitals, and 101 sixth‐year medical students (response rate, 99%). ResultsCrying was frequent in hospitals; 57% of doctors, 76% of nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 7 publications
(2 reference statements)
2
42
3
Order By: Relevance
“…Wagner found that 57% of doctors, 76% of nurses and 31% of medical students had cried at work at least once, generally when identifying suffering or crying with dying patients or their families. Medical students reported the highest percentage of negative social consequences of their crying, sometimes being ridiculed or screamed at 28. It is important to remember that ‘staff grief is real’,29 ‘doctors are moved by the deaths of the strangers for whom they care and are often powerfully affected by the death’ 30 31.…”
Section: Discussionmentioning
confidence: 99%
“…Wagner found that 57% of doctors, 76% of nurses and 31% of medical students had cried at work at least once, generally when identifying suffering or crying with dying patients or their families. Medical students reported the highest percentage of negative social consequences of their crying, sometimes being ridiculed or screamed at 28. It is important to remember that ‘staff grief is real’,29 ‘doctors are moved by the deaths of the strangers for whom they care and are often powerfully affected by the death’ 30 31.…”
Section: Discussionmentioning
confidence: 99%
“…Self-report is often retrospective, with respondents being asked to recollect their crying over a time frame that may range from the past 24 hours (Young, 1937) to the past year Williams, 1982;Williams and Morris, 1996). Alternatively, respondents can be asked to provide a general assessment of their crying frequency with no period of time being specified (De Fruyt, 1997;Lombardo et al, 1983;Wagner et al, 1997). Retrospective self-reporting in general brings problems of inaccurate recall and memory bias (Simon and Von Korff, 1995).…”
Section: The Study Of Cryingmentioning
confidence: 98%
“…Put simply, as in many human relationships, doctors may depersonalize patients because they fear intimacy. Becoming emotionally attached to patients (however marginally) can have its emotional costs, and can frequently serve to invite criticism from other hospital staff (Wagner et al 1997).…”
Section: The Behaviour Of Hospital Staffmentioning
confidence: 98%
“…Moreover, it would appear that medical professionals and students are as sceptical as ever about the true importance of such factors (for example, see Wagner et al 1997). Although the American Psychological Association (APA) recommended the inclusion of psychological content in medical training as far back as 1911 (Rodin and Stone 1987), it was not until the 1960s that behavioural science became signi cantly visible in American medical schools (Matarazzo 1994).…”
mentioning
confidence: 97%